The species of Priopoda Holmgren (Hymenoptera: Ichneumonidae) from China with a key to species known in Oriental and Eastern Palaearctic Regions - Sheng, Mao-Ling; Sun, Shu-Ping (Zootaxa, 2012)
Nine species of Priopoda Holmgren, 1856, are reported from China. Five, Priopoda biconcava Sheng & Sun, sp.n., P.dentata Sheng & Sun, sp.n., P. dorsopuncta Sheng & Sun, sp.n., P. nigrifacialis Sheng & Sun, sp.n. and P. uniconcavaSheng & Sun, sp.n. collected from Jiangxi Province, situated in the northern border of the Oriental part of China, are newto science. Two, Priopoda owaniensis (Uchida, 1930) and P. sachalinensis (Uchida, 1930), are new records for China. A key to species of Priopoda Holmgren known in Oriental and Eastern Palaearctic Region is provided.